Communication Design of Ma’had Al-Jami’ah in Preventing Radicalism in IAIN Salatiga - Yusuf, Muhamad Fahrudin; Miftahuddin, M. (LPPM IAIN Kudus, 2020)
The purpose of this study was to describe how Ma’had Al-Jami’ah designed the message of religious antiradicalism in Institut Agama Islam Negeri (IAIN, State Islamic Institute) Salatiga. In this study, communication design was interpreted as a creative strategy from Ma’had Al-Jami’ah through informative and transformative messages. The strategy started from how the idea was expressed and who would be the messenger. This study used a qualitative method with descriptive case studies. The collecting data techniques in this study were in depth interview, observation, and documentation techniques. The results obtained from this study were that although there is no antiradicalism communication design that is detailed, structured, and massive and is still on a small scale, but efforts to counteract radicalism have been carried out by Ma’had Al-Jami’ah IAIN Salatiga. This is done by the manager, instructor, caregiver and management. Starting from the selection of teachers, the contents of the material, and presenters in a variety of formal and informal activities, updating maqalah (quote) about the love peace message of Islam the WhatsApp group management. The recommendations found in this study are: (1) the importance of a comprehensive explanation of the antiradicalism benefits; (2) revitalizing the role of Ma’had Al-Jami’ah as an antiradicalism agent on campus; and (3) a structured and massive campaign is needed that covered the entire academic community of IAIN Salatiga, given the heterogeneous input of students.